Role of Peroxisome Proliferator-Activated Receptors in Inflammation Control. Issue 3 (29th July 2004) - Youssef, Jihan; Badr, Mostafa
Abstract : Peroxisome proliferator-activated receptors (PPARs) were discovered over a decade ago, and were classified as orphan members of the nuclear receptor superfamily. To date, three PPAR subtypes have been discovered and characterized (PPARα, β / δ, γ ). Different PPAR subtypes have been shown to play crucial roles in important diseases and conditions such as obesity, diabetes, atherosclerosis, cancer, and fertility. Among the most studied roles of PPARs is their involvement in inflammatory processes. Numerous studies have revealed that agonists of PPARα and PPARγ exert anti-inflammatory effects both in vitro and in vivo. Using the carrageenan-induced paw edema model of inflammation, a recent study in our laboratories showed that these agonists hinder the initiation phase, but not the late phase of the inflammatory process. Furthermore, in the same experimental model, we recently also observed that activation of PPARδ exerted an anti-inflammatory effect. Despite the fact that exclusive dependence of these effects on PPARs has been questioned, the bulk of evidence suggests that all three PPAR subtypes, PPARα, δ, γ, play a significant role in controlling inflammatory responses. Whether these subtypes act via a common mechanism or are independent of each other remains to be elucidated. However, due to the intensity of research efforts in this area, it is anticipated that these efforts will result in the development of PPAR ligands as therapeutic agents for the treatment of inflammatory diseases.